PERBEDAAN PENGOLAHAN COOKIES KURMA OVEN DAN KUKUS TERHADAP PERCEPATAN PERSALINAN KALA II - Nina Fitri; Lisa Ramadhani (Maternal Child Health Care, 2022)
Long parturition is one of the causes of maternal and fetal death. By consuming dates before delivery, besides being filling, it is also useful for making the uterine contractions more regular. The purpose of the study was to compare the processing of oven date Cookies and steamed date Cookies to the acceleration of the second stage of labor at BPM Az Jambi City in 2021. This research is a pre-experimental study with two posttest groups. This research was carried out at BPM Azimah Jambi City in July 2021. The population in this study were all mothers who gave birth at BPM Azimah in july-august 2021. The sample of this study used purposive sampling technique. Data collection was carried out by processing and giving oven date Cookies and steamed date Cookies to the second stage of labor and assessing the acceleration of labor. The analysis used is univariate and bivariate. The results showed that the average acceleration of labor in the second stage given oven Cookies was 26.8 minutes, while the average description for the second stage of labor given steamed Cookies was 30.6 minutes. There is no difference in the average acceleration of labor in the second stage of processing oven and steamed date Cookies at BPM A Jambi City in 2021 with a p value of 0.559. It can be concluded that giving oven date Cookies and steamed date Cookies has no difference on the progress of labor. The results of this study can be used as a reference for midwives in providing delivery care in order to meet nutritional intake and hydration during childbirth in helping the progress of labor.  Bibliography : 30 (2010-2019) Keywords : Oven Date Cookies, Steamed Date Cookies, Labor Acceleration